Pengaruh Permainan Puzzle terhadap Kemampuan Memecahkan Masalah Anak Usia Dini - Raihan Abaidata; Elva M Sumirat; Putri Thalib; Ribby Aulia Salsabila; Siti Alizah A. Sua; Riyanti Latama; Ardia Regita Datunsolang; Siti Afrianti S. Labedik; Nur Andini Jois; Sri Yulita Sa’ban; Riska Riska; Nurul Fazrun Dadu; Nur Hasana J. Monomo; Siti Nur Afni Kantoli (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
The purpose of this study was to determine how puzzle games affect the problem-solving abilities of early childhood children. This study used quantitative methods and a quasi-experimental design. The study involved children aged 4 to 6 years from various early childhood education institutions (PAUD). Purposive sampling was used to collect samples. Data were collected through pre-tests and post-tests of problem-solving abilities and observations of children's behavior while playing puzzles. Logical thinking, creativity, concentration, focus, use of problem-solving strategies, and willingness to learn were all metrics used for assessment. To determine the differences in abilities before and after treatment, the collected data were analyzed statistically. The results of the study showed that puzzle game intervention improved children's problem-solving abilities. Children learned to identify problems, make plans for solutions, and work independently. In addition, it was proven that puzzle games as a learning medium were more effective with the help and guidance of teachers and parents. According to this study, puzzle games are an effective tool for developing the cognitive, social, and emotional abilities of early childhood.